The outcome of bone graft surgery for nonunion of fractures of the scaphoid. (September 2019) - Ammori, Mohannad B.; Elvey, Michael; Mahmoud, Samer S.; Nicholls, Alex J.; Robinson, Simon; Rowan, Clare; Spence, Stephanie; Wade, Ryckie G.; Karantana, Alexia; ,; Davis, Tim R. C.
Data on 806 patients undergoing bone graft surgery for a scaphoid fracture nonunion were retrospectively collected at 19 centres in the United Kingdom. Each centre contributed at least 30 cases. Sufficient data were available in 462 cases to study factors that influenced the outcome of surgery. Overall union occurred in at least 69%, and nonunion in at least 22%, with 9% of cases having 'uncertain union status'. Union appeared to be adversely influenced by smoking and the time between acute scaphoid fracture and nonunion surgery, with adjusted odds ratios of 1.8 and 2.4, respectively, but neither achieved the pre-determined significance level of 0.003. The type of bone graft (vascular vs non-vascular; iliac crest vs distal radius) did not appear to influence outcome. Further large multicentre prospective studies with clear definitions of 'union' and other factors are needed to clarify whether modification of surgical technique can influence union. Level of evidence: IV